PENGARUH FINANCIAL LITERACY DAN LIFESTYLE TERHADAP MANAJEMEN KEUANGAN SANDWICH GENERATION DI JAKARTA SELATAN - Abdillah, Diffa U'tsula; Bonnario, Moh; Rina, Nova (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
The sandwich generation in South Jakarta faces dual financial burdens that challenge financial management. This study aims to analyze the effect of financial literacy and lifestyle on financial management. A quantitative method was applied to 370 respondents aged 18–26 using questionnaires and SmartPLS analysis. The results show an R² value of 0.367, indicating that the independent variables explain 36.7% of financial management variation. Hypothesis testing confirmed that financial literacy significantly influences financial management (O = 0.531; T = 7.575; p = 0.000), as does lifestyle (O = 0.204; T = 3.966; p = 0.000). Simultaneously, both variables have a positive effect (O = 0.604; T = 10.149; p = 0.000). The discussion highlights that improving financial literacy plays a more dominant role than lifestyle control in enhancing financial management of the sandwich generation. Keywords : Financial Literacy, Lifestyle, Finansial Management, Sandwich Generation.